MANAJEMEN PENDIDIKAN ISLAM PADA MASA RASULULLAH SAW DAN PADA MASA MODERN - Sidik, Ahmad; Amin, Muhammad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2019)
The purpose of this research is to know how to analyze the management of Islamic education at the time of Rasulullah SAW, knowing how to analyze the management of Islamic education in modern times, and know the comparative analysis of Islamic Education management in the time of Rasulullah SAW and in modern times. Based on the results of the research can be noted that from the author's analysis on the management of Islamic education at the time of Rasulullah SAW can be deduced from planning (planning) that is fundamental to the educational purpose of the friends and this people only one, that is the moral remedy, and it is a vision of education in it. Organizing (organizing), at the time of Rasulullah SAW organizing which became the strength of the Dicala is the trust and spirit in implementing the trust given to the companions actuating (Implementation), at the time of Rasulullah SAW implementation is done in the process of education is to try the professional and try without complaining controlling (supervision) at the time of Rasulullah SAW supervision.